Pengaruh Return on Assets, Leverage dan Firm Size terhadap Tax Avoidance pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2021 - One Yantri (Reviu Akuntansi, Manajemen, dan Bisnis, 2022)
Purpose: This research aims to determine the effect of the (1) return on assets, (2) leverage and (3) firm size partially on tax avoidance in energy sector companies listed on Indonesian stock exchange for the period 2016-2021. In addition, this research also aims to determine the effect of (4) return on assets, leverage, and firm size simultaneously on tax avoidance in energy sector companies listed on the Indonesian stock exchange for the perioed 2016-2021. Methodology: This research is ex post facto. The population of this research are energy sector companies listed on Indonesian stock exchange for the period 2016-2021. The sampling technique used was purposive sampling method , which is the data were selected based on certain criteria. Based on predetemined criteria, total sample 15 companies was obtained. The type of the data used is secondary data obtained from the Indonesian capital market directory. Classical assumption test involved normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. The data analysis used were double linear regression aanalysis, t test partial and f test simultan. Results: The result of this study indicate that (1) Return on assets has a negative and sifnificant effect on tax avoidance. This is indicated by the tcount -3.038 and the significance value 0.003 < 0.05, which means that the return on assets has a sinificant negative effect on tax avoidance. (2) Leverage was projected with Debt to equity ratio has not a significant negative effect on tax avoidance. This is indicated by the tcount -0.685 and the significance value 0.495 > 0.05, which means that the debt to equity ratio has not a sinificant negative effect on tax avoidance. (3) Firm Size has not a significant positive effect on tax avoidance. This is indicated by the tcount 1.407 and the significance value 0.163 > 0.05, which means that firm size has not a significant positive effect on tax avoidance. (4) Return on assets, leverage and firm size simultaneously effect on tax avoidance. This is indicated by the significance of 0.13 < 0.05.